Kajian Filologis dan Resepsi Kitab Tambeh Tujoh Blah 17 dalam Tradisi Islam Aceh - Alfian Alfian; Muhammad Haikal; Muhammad Al-Farisy (Universitas Negeri Gorontalo, 2026)
The arrival of Islam in Aceh initiated a process of Islamization that influenced nearly all aspects of life, including arts and culture. One significant impact was the adoption of the Malay Arabic script (harah Jawoe) for writing in Malay and Acehnese, leading to the development of local Islamic literary traditions such as hikayat, tambeh, and nazam. This study aims to examine the role and position of Tambeh Tujoh Blah 17 within Aceh’s Islamic literary heritage, as well as its connection to the Islamization process and the formation of local Islamic identity. The research employs philological methods to trace the origins, manuscript variants, and linguistic characteristics of the text, combined with reception analysis to understand its acceptance and usage in the community. The findings reveal that Tambeh Tujoh Blah 17 contains teachings on faith (aqidah), jurisprudence (fiqh), and ethics (akhlaq), while serving as a medium for internalizing Islamic values into Acehnese socio-cultural life. The text was studied in dayah, meunasah, and through oral transmission, becoming an integral part of traditional Islamic education. This study underscores the tambeh’s role as an effective medium of Islamic propagation and as a reflection of local Islamic identity. It contributes to the preservation of Aceh’s intellectual heritage and enhances understanding of Islamization dynamics through literature.